D-(-)-Lactic acid production from cellobiose and cellulose by Lactobacillus lactis mutant RM2-24 - Singhvi, Mamta; Joshi, Dipti; Adsul, Mukund G.; Varma, Anjanikumar; Gokhale, Digambar V. (Green Chemistry, 2010)
Lactobacillus lactis mutant RM2-24 utilizes cellobiose efficiently, converting it into D-(-)-lactic acid. Cellobiose-degrading enzyme activities were determined for whole cells, cell extracts and disrupted cells. Aryl-beta-glucosidase activity was detected in whole cells and disrupted cells, suggesting that these activities are confined to the cells. The mutant produced 80 g l(-1) of lactic acid from 100 g l(-1) of cellobiose with 1.66 g l(-1) h(-1) productivity. Production of D-lactic acid from different cellulose samples was also studied. The cellulose samples at high concentration (10%) were hydrolyzed by cellulase enzyme preparation (10 FPU g(-1) cellulose) derived from Penicillium janthinellum mutant EU1 generated in our own laboratory. We obtained a maximum 72% hydrolysis, yielding glucose and cellobiose as the main end products. Lactic acid was produced from these cellulose samples by simultaneous sacchari. cation and fermentation (SSF) in a media containing a cellulase enzyme preparation derived from Penicillium janthinellum mutant EU1 and cellobiose utilizing Lactobacillus lactis mutant RM2-24. A maximum lactic acid concentration of 73 g l(-1) was produced from a concentration of 100 g l(-1) of bagasse-derived cellulose, the highest productivity and yield being 1.52 g l(-1) h(-1) and 0.73 g g(-1), respectively. Considering that bagasse is a waste material available in abundance, we propose to use this biomass to produce cellulose and then sugars, which can be fermented to valuable products such as ethanol and lactic acid.